The The Influence of Smart Box Media on Basic Mathematical Skills in Children Aged 5-6 Years - Ernawati, Meilisa; Madyawati, Lilis; Astuti, Febru Puji (Universitas Muhammadiyah Magelang, 2026)
This study aims to determine the effect of Smart Box Media on basic mathematical skills. The research design is pre experimental with a one group pre test and post test model. The sample was selested using purposive sampling. The subjects of this study were 10 children aged 5 to 6 years at Pertiwi Gondowangi Kindergarten, Sawangan District, Magelang Regency. This study used a quantitative approach with an experimental design. Mathematical ability was measured using an observation sheet. Data analysis using Wilcoxon analysis showed that the significance value was 0,000 < 0,05 , so Ho was rejected and Ha was accepted, meaning that there was a difference between the pre test and post test result. It can be concluded that Smart Box Media Affects the Basic Mathematical Skills of Children Age 5- 6 Years.